ANTIDIABETIC ACTIVITY OF INDIAN MAHAGONI PLANT EXTRACT BY TRANSDERMAL THERAPY - R, Stephan; S, Jeyabharathi; N, Jeenathunisa; Priscilla H, Deena (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Most of the medicinal products are originated from nature and considered as a rich source for producing herbal drugs with modern approach. Swietenia mahagoni is one of the most important plants of the Meliaceae family. This plant has been reported to treat diabetes without adverse effects by local communities since long time. The present work is aimed on the transdermal therapy using seed extract of S. mahagoni in streptozotocin (STZ)-induced diabetes mellitus in male Wistar rats. Methods: The induction of diabetic state by STZ injection and the biochemical analyses such as blood glucose, serum protein, albumin, cholesterol, urea, and alkaline phosphatase was monitored before and after treatment. Results: This present study showed there was a significant (p<0.01) increase in the blood glucose level in diabetics, as well as, diabetics treated with insulin transdermally. However, there was significant reduction (p<0.05) in the hyperglycemic state in diabetic animal, which is transdermally treated with seed extract. Conclusion: Thus, the results showed that this type of drug delivery could provide a pain-free physiological insulin balance among the patients.